Surface modification of activated carbon for adsorption of SO2 and NOX: A review of existing and emerging technologies. (October 2018) - Abdulrasheed, A.A.; Jalil, A.A.; Triwahyono, S.; Zaini, M.A.A.; Gambo, Y.; Ibrahim, M.
Abstract: A severe problem associated with combustion of fossil fuels and biomass in the quest for heat and power generation is the release of acidic gases. This posed great health and environmental concerns, and their presence in sufficient amount in flue gas affects the performance of CO2 capture system through formation of heat resistant salts on reaction with the capture medium. Among the various alternatives, removal of the SO2 and NOx gases by adsorption on surface modified activated carbon from renewable sources has proven to be an efficient and robust technology which is attributed to the presence of immobilized chemical species on the carbon surface providing the necessary affinity with the target gaseous pollutants. Thus, the present review aimed at providing a cutting-edge critical assessment of research outputs on SO2 and NOx adsorption from flue gas by surface modified activated carbon. Conspicuously, modification mechanisms, surface characterization, surface chemistry and application of surface modification of activated carbon were discussed elaborately.